ECHINOCOCCUS GRANULOSUS MULTISYSTEMIC INFECTION – INFLUENCE OF SOCIO-ECONOMIC FACTORS ON PROGNOSIS - Irina Dijmărescu; Adrian Dijmărescu; Alexandra Popârlan-Constantin; Alexandra Coroleucă (Romanian Journal of Oral Rehabilitation, 2020)
Introduction: Echinococcus granulosus eggs` ingestion leads to the parasitosis known as echinococcosis. Case report: At age 11 the teenager was admitted for anaphylactic shock (rupture of a hydatid cyst in his right lung, removed together with the medium lobe). Five years later he was admitted for thoracic pain. CT performed at that point showed multiple cystic lesions (pulmonary parenchyma, pleura, liver, subcutaneous tissue). Patients` parents did not agree with the surgical removal of the lesions. After 6 months he presented with respiratory distress after a thoracic traumatism (car accident). Chest X-ray showed multiple lesions with air-fluid levels in the right lung. CT showed multiple cystic masses, some of them ruptured and partially evacuated, in both lungs, mediastinum and peritoneum, associated with pleural effusion. Conclusions: We report the case of a teenager diagnosed with a curable parasitic infection during childhood which unfortunately became untreatable due to non-medical factors.